#TITLE_ALTERNATIVE# - O. (NIM 10103058), PANGIHUTAN
Reliability is a branch of statistic that is used for product quality and maintenance. There are two kinds of system that is commonly used in reliability, repairable system and nonrepairable system. Formally, the kind of system that frequently used is repairable system, but component of this system is nonrepairable system. This work discusses the analize of power law process model for repairable system , specially reliability and nonhomogenous poisson process. There are two testing methods that are used for this model, duane plot for graphical method and Cramer-von Mises test for statistics method with 5% significant level.